Legal Protection for Creative Economic Actors of Intellectual Property as the Debt Guarantee - Brina Saskya Paramita; Aldira Mara Ditta (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2024)
The development of the creative economy often experiences problems such as limited access to capital; with the enactment of Government Regulation No. 24 of 2022 concerning the Creative Economy, the government facilitates Intellectual Property-Based Financing Schemes through financial services institutions, but in its implementation, there is a need for legal protection for creative economy actors who want to get a source of financing, besides that many people do not understand how the requirements for filing Intellectual Property-based financing due to the intangible nature of the collateral object. This research uses the normative juridical method. This research uses all laws and regulations to examine more deeply related to the research in question. The research results indicate that the requirements for applying for an Intellectual Property-Based Financing Scheme must be registered and have a certificate from the Directorate General of Intellectual Property. Intellectual Property (IP) in question is copyright and patent rights based on Article 16 paragraph (3) of the Copyright Law and Article 108 of the Patent Law. Legal protection of creative economy actors in the Intellectual Property-Based Financing Scheme has been pursued by the government, including the existence of further regulations issued by the Financial Services Authority, which makes creative economy actors avoid conflicts or financing disputes through insurance contracts, preventing theft of ideas by others, providing incentives from the government to register IP, providing legal assistance before the court process, and providing legal assistance in the event of a financing dispute.